Determination of the mechanism and extent of surface degradation in Ni-based cathode materials after repeated electrochemical cycling - Hwang, Sooyeon; Kim, Se Young; Chung, Kyung Yoon; Stach, Eric A.; Kim, Seung Min; Chang, Wonyoung (AMER INST PHYSICS, 2016)
We take advantage of scanning transmission electron microscopy and electron energy loss spectroscopy to investigate the changes in near-surface electronic structure and quantify the degree of local degradation of Ni-based cathode materials with the layered structure (LiNi0.8Mn0.1Co0.1O2 and LiNi0.4Mn0.3Co0.3O2) after 20 cycles of delithiation and lithiation. Reduction of transition metals occurs in the near-surface region of cathode materials: Mn is the major element to be reduced in the case of relatively Mn-rich composition, while reduction of Ni ions is dominant in Ni-rich materials. The valences of Ni and Mn ions are complementary, i.e., when one is reduced, the other is oxidized in order to maintain charge neutrality. The depth of degradation zone is found to be much deeper in Ni-rich materials. This comparative analysis provides important insights needed for the devising of new cathode materials with high capacity as well as long lifetime. (C) 2016 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution (CC BY) license.
Keywords: LITHIUM-ION BATTERIES; ENERGY-LOSS SPECTROSCOPY; ELECTRON-MICROSCOPY; LI; OXIDES; CAPACITY; LI1.2NI0.2MN0.6O2; RECONSTRUCTION; PERFORMANCE; EVOLUTION